Pemilihan Penyedia Jasa Konstruksi via e-katalog menggunakan metode AHP - Vero Andron; Khadavi; Wahyudi Utama Putra (Jurnal Konstruksi, 2025)
This study aims to analyze and develop a decision-making system for selecting construction service providers through the e-purchasing mechanism (construction e-catalog) for construction works, using the Analytic Hierarchy Process (AHP) method. The AHP method is employed to identify and rank criteria as well as alternative construction service providers based on weighted assessments derived from factors such as technical requirements, price, company experience, financial capacity, and supplier relations. The use of the construction e-catalog as a medium for selecting service providers is expected to improve efficiency, transparency, and accountability in the government procurement process. The results of the study indicate that technical requirements (weight: 0.296) are the most crucial factor in selecting construction service providers. This highlights the importance for providers to pay special attention to technical requirements, which include two key components: managerial personnel and main equipment. Managerial personnel must be competent in carrying out construction works, while physical company resources, such as reliable heavy equipment and high-quality materials, are essential to ensure optimal performance.